A Review of Soybean Oil Lipid Oxidation and Its Prevention Techniques - Rossi Indiarto, Muhammad Abdillah Hasan Qonit (International Journal of Advanced Science and Technology, 2020)
Soybean is a category of fatty acid-rich grains. The commodity highly contains palmitate, stearic, oleic, linoleic, and linoleic fatty acids. However, high fatty acid levels trigger soybean oil to oxidize. This oxidation contributes to product quality degradation, storage stability, and essential fat content. Besides, oxidation produces radical compounds that are harmful to health. Autoxidation (auto-oxidation) is common in high oil content substances when oxygen and unsaturated fatty acids react. Adding antioxidants is an effort to overcome these problems. Antioxidants can break the chain of free radical formation. Also, genetic approaches may be used to produce soybean plants with high oxidative stability using lipid interesterification.